2015
DOI: 10.1108/ejtd-04-2015-0031
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal, mixed method evaluation of self-awareness training in the workplace

Abstract: Purpose – The purpose of this study is to investigate whether self-awareness, which is associated with general well-being and positive life outcomes, is also of specific benefit in the workplace. The authors tested the relationship between self-awareness and job-related well-being, and evaluated two different interventions designed to improve dispositional self-awareness at work. Design/methodology/approach – Full-time employees took par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 26 publications
1
64
0
Order By: Relevance
“…However, in the case of some of the interventions, changes in well-being were treated as a measure of the effectiveness of a learning intervention. Of the 41 studies, 12 did not seek to measure learning outcomes that were distinct from well-being, simply measuring the effectiveness of the learning intervention by its impact on well-being outcomes ( Vitzthum, Klapp, & Groneberg, 2015;Romanowska et al, 2011;Shonin, Van Gordon, Dunn, Singh, & Griffiths, 2014;Sutton, Williams, & Allinson, 2015;Taniguchi, Hirokawa, Tsuchiya, & Kawakami, 2007;Varekamp, Verbeek, de Boer, & Van Dijk, 2011;Williams, Brenner, Helms, & Williams, 2009;Zijlmans, Embregts, Gerits, Bosman, & Derksen, 2015). The rest of the studies measured both learning and well-being outcomes, although there was often a good deal of overlap between the two.…”
Section: Resultsmentioning
confidence: 99%
“…However, in the case of some of the interventions, changes in well-being were treated as a measure of the effectiveness of a learning intervention. Of the 41 studies, 12 did not seek to measure learning outcomes that were distinct from well-being, simply measuring the effectiveness of the learning intervention by its impact on well-being outcomes ( Vitzthum, Klapp, & Groneberg, 2015;Romanowska et al, 2011;Shonin, Van Gordon, Dunn, Singh, & Griffiths, 2014;Sutton, Williams, & Allinson, 2015;Taniguchi, Hirokawa, Tsuchiya, & Kawakami, 2007;Varekamp, Verbeek, de Boer, & Van Dijk, 2011;Williams, Brenner, Helms, & Williams, 2009;Zijlmans, Embregts, Gerits, Bosman, & Derksen, 2015). The rest of the studies measured both learning and well-being outcomes, although there was often a good deal of overlap between the two.…”
Section: Resultsmentioning
confidence: 99%
“…As this was a cross-sectional study, it is not possible to identify whether trait reflection is the cause of greater experience of reflective self-development or whether reflective self-development results in an increase in trait reflection. However, previous work has indicated that engagement in self-awareness training can indeed have some impact on trait reflection (Sutton, Williams, & Allinson, 2015) and it seems likely that reflection and development interact closely: increased reflection results in increased self-development, which in turn promotes higher levels of trait reflection in the long term.…”
Section: Discussionmentioning
confidence: 98%
“…Sutton et al (2015) report on a longitudinal study of the effects of workshops designed to enhance self-awareness and identify four main themes and twelve contingent themes in the outcomes that participants report. Two of these twelve contingent themes were excluded from this study as not relevant: ‘no changes’ was excluded as the SAOQ is designed to measure only reported effects of self-awareness and ‘future development’ because the theme involved hopes or plans about future development which was not yet in evidence.…”
Section: Methodsmentioning
confidence: 99%
“…All multiple organization studies report the number of respondents and, where practicable, the size of the population from which they are selected or the associated response rate, very little commentary being provided. Lists compiled by the researcher are used for three multiple organization studies (Table ), being developed from: “multiple publicly available business directories” (Au & Ahmed, , p. 354), professional development bodies serving a specific sector (Fontana et al, ) and researchers’ contacts and word of mouth (Sutton, Williams, & Allinson, ). As before, associated issues are very rarely discussed, at best receiving a brief comment; for example, “Although the response rate is low, there is no reason to believe that the sample is unrepresentative of the overall population” (Fontana et al, , p. 38).…”
Section: Gaining Physical Access In Hrd Survey Researchmentioning
confidence: 99%